Detection of chemical elements related to impurities leached from raw sugarcane: Use of laser-induced breakdown spectroscopy (LIBS) and chemometrics - Andrade, Daniel Fernandes; Guedes, Wesley Nascimento [UNESP]; Pereira, Fabiola Manhas Verbi [UNESP] (Elsevier, 2018)
Impurities in raw sugarcane directly influence the quality of sugarcane juice by compromising its color and affecting the entire sugar manufacturing process. Therefore, the primary objective of this study was to identify the chemical elements related to different levels of impurities, ranging from 3 to 10 wt%, leached from sugarcane using only water. This analysis employed laser-induced breakdown spectroscopy (LIBS) after the sample solutions were immobilized in a polyvinyl alcohol (PVA) polymer. A mixture design was outlined to describe the composition of numerous samples. To treat the data generated by LIBS, 12 different standardization strategies of the dependent variables (LIBS instrumental response) were tested. To identify the chemical elements from the impurities and their relations, a principal component analysis (PCA) was performed using the entire spectra. The analysis of the score plots shows a large segregation in the experiments with the highest amounts of impurities (from 8 to 10 wt%). Calcium, and Mg were highly correlated to the samples in the PCA and the ratio between the highest intensity of these signals for samples and 10% (w/v) PVA confirmed this evidence. LIBS showed advantages in the analysis of impurities from sugarcane after the conversion of the PVA solution into a solid to contain the leached solutions. The method provides a fast, simple and sensitive method for the detection of sugarcane impurities.
Keywords: Chemometrics; Clarification; Laser-induced breakdown spectroscopy; Mixture design; Standardization modes; Sugarcane